Resiliensi Ibu dari Keluarga Ekonomi Lemah di Kabupaten Kepulauan Meranti - Ria Novianti; Febrialismanto; Ilga Maria (Aṭfāluna: Journal of Islamic Early Childhood Education, 2019)
Mothers have multi-task that must be done every day. Household problem, work problem and also the economic problem experienced by many mothers in the District of Kepulauan Meranti became the causes of stress experienced by mothers that affect how she respond the environment, also affect the child rearing. The ability to deal with problems is called resilience. This study aims to examine the resilience of mothers who come from low income families in the District of Kepulauan Meranti. This study used descriptive quantitative method. Sampling method used is random sampling and there are 70 mothers as sample. It was found that the mother's resilience was 73,03%. Mothers in Kepulauan Meranti District is resilience eventough they have ti struggle with many stressfull condition. The support from spouse and relatives which offer the positive relationship help mothers to overcome stress and become resilience. Mother need to be resilient to deal with her multi-task, mainly in child rearing.